[Newsletter] - 4 Korners Family Resource Center (2015)

McGill Program Networks Creating Impacts - Buffitt, Kimberly (2015)

The East Island Retention of Health Professionals Project – English, An Asset! : REISA Internships - A Success Story - Gatre Guemiri, Fatiha; Zappitelli, Juliana; Mirtaheri, Mina; Granner, Francine; Hendrickson-Nelson, Mary (2015)

[Newsletter] - 4 Korners Family Resource Center (2015)

Accès interrégional aux services sociaux et de santé pour les personnes d'expression anglaise de l'est de Québec - Richardson, Mary (2015)
Keywords: Official Language Minority Community (OLMC)

Inter-regional Access to Specialized Health and Social Services for English-speakers from Eastern Quebec - Richardson, Mary (2015)
Keywords: Official Language Minority Community (OLMC)

[Newsletter] - 4 Korners Family Resource Center (2015)

Socio-demographic Characteristics of Visible Minorities in Quebec's English-speaking Communities - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for xyz. The variables covered are: - Gender - Age structure - Household living arrangements - Recent mobility - Educational attainment - Labour force activity - Income - Low-income cut-off

Inter-Regional Access to Specialized Health and Social Services for English-speakers from Eastern Quebec - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This project was developed to better understand the experience and needs of English speakers from the eastern regions of Quebec (Gaspésie - Îles-de-la-Madeleine, the North Shore, including the Lower North Shore, and the Lower Saint-Lawrence) as concerns extra-regional health and social services. The specific challenges facing this official language minority community were known only anecdotally, but needed to be better understood before effective action could be taken to address the needs of this population.
Keywords: Official Language Minority Community (OLMC)

Mental Health Resource Guide for the Gaspé Coast and Magdalen Islands - Dow, Cynthia; Harrison, Kim; Payette, Tom; Synnott, Jessica (2015)

A Road Map to your Caregiving Journey : A Practical Handbook for English-speaking Caregivers in the Great Quebec City Region - Jeffery Hale Community Partners (2015)

Action prévention : La sécurité est notre responsabilité à tous - Haberlin, John (2015)

The Policy on Language of Service - Jeffery Hale - Saint Brigid's (JHSB) (2015)
The objective of this policy is to ensure that employees communicate effectively with both French and English‐speaking clients and that Language Assistance Services are also available for other Limited‐French or English Proficient (LFEP) individuals and their surrogate decision‐makers at all points of contact, in a timely fashion and in their preferred language in order to ensure an understanding of their health condition and treatment options.

Canadian Community Health Survey (2011-2012) : Findings Related to the Mental and Emotional Health of Quebec's English-speaking Communities - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This report is organized around two primary objectives. The first objective is to provide reliable knowledge regarding the mental and emotional health of Quebec’s English-speaking minority communities. In so doing, this report contributes up-to-date and relevant findings to the evidence base that informs the decision-making and initiatives of organizations serving this population. This objective is served by 131 statistical tables and descriptive commentary that provide information drawn from the 2011-2012 Canadian Community Health Survey (CCHS). The second objective is to consult the body of experience and expertise of community organizations and networks many of whom are on the front-line in meeting the needs and building the resiliency of English speakers in this aspect of their health and well-being. This objective has been met by soliciting the response of five organizations to the picture of the situation among English speakers conveyed by the CCHS tabulations. As a panel, the organizations were invited to address how this knowledge might serve as a resource in setting priorities and designing initiatives benefitting English-speaking communities. In other words, as a tool in developing community capacity.
Keywords: Official Language Minority Community (OLMC)

Language Access Policy : Planning & Implementation Guide - Prata, Ghislaine (Jeffery Hale - Saint Brigids (JHSB), 2015)
Jeffery Hale – Saint Brigid’s (JHSB) is a public, bilingual institution under participatory governance dedicated to providing safe, compassionate and high quality care. Among the strategic objectives of the organisation are the promotion of linguistic duality and openness to cultural diversity. Recognizing that language access is an integral component of the delivery of high quality and safe health services, JHSB has developed a number of policies, procedures and tools in the area of linguistic access. The organisation is currently seeking to consolidate and develop these initiatives within the framework of a comprehensive language access policy. This report provides a theoretical model and reference to practical tools to inform organisational efforts in the development of a language access policy and the implementation and continuous improvement of a language access plan.
Keywords: Official Language Minority Community (OLMC)

Îles-de-la-Madeleine : Portrait de la communauté d'expression anglaise - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
Le présent portrait a été réalisé en collaboration avec de nombreux partenaires locaux, à l’initiative du Conseil des anglophones madelinots (CAMI) et avec l’appui du Réseau communautaire de santé et de services sociaux (RCSSS). Parmi les autres groupes ayant participé au processus figurent la Municipalité de Grosse-Île, l’école de Grosse-Île, la Corporation d’employabilité et de développement économique communautaire (CEDEC), le Centre scolaire communautaire (CSC) et l’Agglomération des Îles (comité de développement social/Les Îles en Forme).

Portrait of the English-speaking Community of Rouyn-Noranda - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed by Neighbours and the Community Health and Social Services Network (CHSSN), in collaboration with the Centre intégré de santé et des services sociaux (CISSS), the city of Rouyn-Noranda (Villes et villages en santé) and the local English school, Noranda School. Neighbours is a non-profit community organization established to serve the Englishspeaking population of the Rouyn-Noranda area through facilitating information sharing, defending the right of access to service in English and organizing social and cultural events. Neighbours is committed to strengthening networks within the English and French speaking population as well as encouraging community development initiatives. The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of Rouyn-Noranda in order to address the issues it faces.
Keywords: Official Language Minority Community (OLMC)

Portrait of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed in collaboration with many local partners, through the initiative of the Council for Anglophone Magdalen Islanders (CAMI), with support from the Community Health and Social Services Network (CHSSN). Other groups involved in this process include the municipality of Grosse-Ile, the Grosse-Ile school, the Community Economic Development and Employability Corporation (CEDEC), the Community Learning Centre (CLC), Agglomération des Îles (social development committee/Les Îles en Forme).

Community Vitality Survey of the English-speaking Community of Quebec - Community Health and Social Services Network (CHSSN) (2015)

[Carter Statement] - The English Speaking Catholic Council (ESCC) (2015)

The McGill Retention Bursary Program: Evaluation Report : Training and Retention of Health Professionals Project - Gagnon, Marie-Pierre; Lampron, Amélie (CHU de Québec Research Centre, 2015)
An evaluation of this bursary program was conducted, focusing on the components of the program (e.g. eligibility criteria, selection process, etc.) and its outcomes (e.g. recipient intention to return to or stay working in a selected Quebec region at the end of their training, potential impact of the bursary program on retention of health professionals in English-speaking communities, etc.). The objectives of the evaluation were 1) to describe the current processes related to the functioning of the McGill Retention Bursary Program; 2) to explore recipients’ experience of this bursary program; 3) to explore community networks’ experience regarding their collaboration with this bursary program; 4) to assess the effectiveness of the bursary program; and 5) to propose potential improvement strategies for the bursary program currently in place.

Blazing a Trail for Active and Healthy Aging: An Action Plan for Quebec’s English-speaking Seniors 2010-2015 / Tracer la voie pour vieillir en santé et demeurer actif : Plan d’action à l’intention des aînés d’expression anglaise du Québec 2010-2015 - Quebec Community Groups Network (QCGN) (2015)

The English-speaking Population of des Collines-de-l'Outaouais : a Community Portrait - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed by Connexions and the Community Health and Social Services Network (CHSSN), in collaboration with the Centre intégré de santé et de services sociaux des Collines de l’Outaouais (CISSSO). Connexions (the Connexions Resource Centre) is a not-for-profit community organization whose mission is to serve and promote the health, well-being and vitality of the English-speaking population of the Outaouais. It is committed to strengthening networks within the English and French speaking population as well as encouraging community development initiatives.